â€œPROTOTYPE PLTB TURBIN VERTIKAL SAVONIUS-DARRIEUS DENGAN MODUL CHARGER DAN MONITORING BERBASIS IOTâ€ - Rivan Daniel Malau; Catra Indra Cahyadi; Ferry Budi Cahyono (Smart Education, 2025)
Abstract: Promotion is an activity carried out to convey, disseminate, and offer products, so that potential consumers are interested in buying. In the implementation of the promotion, CV. Pentaland Jaya abadi uses website media and brochures that still contain 2-dimensional images and information about housing so that potential consumers are less interested because consumers cannot see the exterior and interior shapes directly. Potential consumers usually get brochures through project locations that are still under construction, after that contact the marketing department. One way to solve this problem can be to use augmented reality technology with the appropriate development method is the Multimedia Development Life Cycle (MDLC) which includes Concept, Design, Material Collecting, Assembly, Testing, and Distribution so that this research can produce an android-based augmented reality application that can display 3 dimensional virtual shapes from 3 housing estates including calista haus, grand ayahanda residence and calista homey. From each housing produces 3 dimensional objects on the exterior and interior so that it can provide interest in buying house objects and in addition to that it also helps in the marketing department in promoting housing objects without the need to show many miniatures that require time and also large places.Â Keywords: Wind Power Plant, Internet of Things, Blynk, ESP32, Charging Module. Abstrak: Penelitian ini bertujuan merancang dan mengimplementasikan prototipe PLTB turbin vertikal tipe Savoniusâ€“Darrieus yang dilengkapi modul charger dan sistem monitoring berbasis Internet of Things untuk mendukung pembelajaran energi terbarukan. Sistem ini menggunakan generator DC 12â€“24 V, baterai lithium 12 V, serta mikrokontroler ESP32 yang terhubung dengan sensor INA219, sensor tegangan, dan sensor RPM berbasis IR. Data hasil pengukuran ditampilkan melalui LCD dan dikirim secara real-time ke platform Blynk melalui koneksi Wi-Fi. Pengujian menunjukkan prototipe mampu menghasilkan tegangan tanpa beban 24 V dan berbeban 12 V, dengan arus maksimum 1,3 mA serta daya listrik 4,0 mW, sementara daya angin teoritis mencapai 9,68 W. Koefisien daya tertinggi tercatat 0,00041 dengan efisiensi konversi 0,041%. Hasil ini membuktikan bahwa integrasi turbin angin vertikal hybrid, modul charger, dan IoT dapat diterapkan secara efektif meskipun kapasitas daya masih rendah dan memerlukan perbaikan desain untuk peningkatan performa.Â Kata kunci: PLTB, Internet of Things, Blynk, ESP32, Modul Charger.